1984
DOI: 10.1128/jvi.51.3.571-577.1984
|View full text |Cite
|
Sign up to set email alerts
|

Replication and recombination in adenovirus-infected cells are temporally and functionally related

Abstract: We have studied the temporal and functional relationships between DNA replication and recombination in adenovirus-infected cells by using Southern blot hybridization to detect recombinant products among intracellular viral genomes. The data show that recombination can be detected soon after DNA replication has commenced and that the proportion of recombinant products increases thereafter. To determine the functional relationship between DNA replication and recombination, replication was blocked with the protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…The absence of Top3 in mitosis leads to the accumulation of cells with an undivided nucleus in the neck of an elongated bud (Gangloff et al ., 1994b). The associated cell cycle delay at the G 2 –M transition is consistent with an impediment of chromosome segregation, suggesting that Top3 is involved directly in the separation of replicated chromatids or, alternatively, in the resolution of topological structures resulting from either recombination during replication or collapsed replication forks (Young et al ., 1984; Kawasaki et al ., 1994; Zou and Rothstein, 1997). Because no noticeable difference in the timing of diploid spore formation could be detected when meiotic levels of recombination are abolished, we do not believe it likely that Top3 plays a meiotic‐specific role in the DNA synthesis process.…”
Section: Discussionmentioning
confidence: 84%
“…The absence of Top3 in mitosis leads to the accumulation of cells with an undivided nucleus in the neck of an elongated bud (Gangloff et al ., 1994b). The associated cell cycle delay at the G 2 –M transition is consistent with an impediment of chromosome segregation, suggesting that Top3 is involved directly in the separation of replicated chromatids or, alternatively, in the resolution of topological structures resulting from either recombination during replication or collapsed replication forks (Young et al ., 1984; Kawasaki et al ., 1994; Zou and Rothstein, 1997). Because no noticeable difference in the timing of diploid spore formation could be detected when meiotic levels of recombination are abolished, we do not believe it likely that Top3 plays a meiotic‐specific role in the DNA synthesis process.…”
Section: Discussionmentioning
confidence: 84%
“…Second, replication and recombination appear to be functionally linked in that Sarisky and Weber showed that inversion events are mediated by the viral DNA replication machinery (50). Third, a precedent exists for a linkage between replication and recombination in other DNA viruses such as T4 (36) and adenovirus (69).…”
Section: Discussionmentioning
confidence: 99%
“…was UV irradiated to stimulate illegitimate recombination. This might be expected from the association of adenovirus recombination with its replication (Young et al, 1984). Apparently, d1312 DNA was a stable, inert episome in 253J cells, 549 cells, or fibroblasts.…”
Section: Effect On Cell Viabilitymentioning
confidence: 96%